Population Education Accessions List. January-April 1997 - United Nations Educational, Scientific and Cultural Organization, Bangkok (Thailand). Principal Regional Office for Asia and the Pacific; United Nations Educational, Scientific and Cultural Organization, Bangkok (Thailand). Principal Regional Office for Asia and the Pacific ([S.l.] : Distributed by ERIC Clearinghouse, 1997)
This bibliography addresses the subject of population education. Entries are categorized into three parts. Part 1, "Population Education," consists of titles of books and other documents addressing various aspects of population education arranged by country in the first section and general materials in the second section. Part 2, "Knowledge Base Information," consists of titles on the different multidisciplinary aspects of population education. These entries are grouped into sections of the following major multidisciplinary topics: (1) Documentation; (2) Education (including environmental education, functional literacy, family planning, AIDS, and sexuality); (3) Environment; (4) Fertility and Family Planning; (5) Health and Nutrition; (6) Information and Communication; (7) Migration, Urbanization, and Human Settlement; (8) Population Policy and Trends; (9) Research and Evaluation; (10) Socio-economic Factors and Conditions; and (11) Women. Part 3, "Audiovisual Materials," consist of titles of various kinds of audiovisual aids (films, slides, charts, kits, videotapes, etc.) having to do with knowledge base and aspects of population education. Appendices contain a list of publishers and sources as well as indexes. Each entry or title is given a running number and bibliographical references that include either the author or corporate author, title, imprint, collation, subject key words, country key words, and classification number. A source code is also given. (PVD)
Availability: UNESCO Principal Regional Office for Asia and the Pacific, P.O. Box 967, Prakanong Post Office, Bangkok 10110, Thailand.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Audiovisual Aids; Elementary Secondary Education; Family Planning; Foreign Countries; Higher Education; Information Sources; Instructional Materials; Population Education; Population Trends; Preschool Education; Resource Materials; Sustainable Development; UNESCO; Reference Materials, Bibliographies